1997
DOI: 10.1094/cchem.1997.74.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Variation for Starch Gelatinization, Pasting, and Gelation Properties in Wheat

Abstract: Cereal Chem. 74(1):63-71The starch of wheat (Triticum aestivum L.) flour affects food product quality due to the temperature-dependent interactions of starch with water during gelatinization, pasting, and gelation. The objective of this study was to determine the fundamental basis of variation in gelatinization, pasting, and gelation of prime starch derived from seven different wheat cultivars: Kanto 107, which is a partial waxy mutant line, and six near-isogenic lines (NILs) differing in hardness. Complete pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
180
3
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(205 citation statements)
references
References 23 publications
(30 reference statements)
15
180
3
7
Order By: Relevance
“…No entanto, neste trabalho, não foi observada qualquer diferença significativa para o teor de amilose total entre os diferentes genótipos de trigo, nem tampouco qualquer correlação entre teor de fósforo e teor de amilose total como também observado por SEIB 30 41 .…”
Section: Teores De Amilose Total E Amilose Complexada Com Lipídeosunclassified
“…No entanto, neste trabalho, não foi observada qualquer diferença significativa para o teor de amilose total entre os diferentes genótipos de trigo, nem tampouco qualquer correlação entre teor de fósforo e teor de amilose total como também observado por SEIB 30 41 .…”
Section: Teores De Amilose Total E Amilose Complexada Com Lipídeosunclassified
“…These applications of starch depend on its physicochemical properties, which depend on many factors, including the ratio of amylose to amylopectin. The cooking properties of many flours also are determined by the physicochemical characteristics of their starches (Shibanuma et al, 1996;Zeng et al, 1997;Noda et al, 2001), which are correlated closely with the staling properties of bread flours and the cooking quality of noodles (Collado and Corke, 1997;Boggini et al, 2001;Noda et al, 2001). We examined the physicochemical properties of the starches from the potato lines expressing GBSSIa and GBSSIb to determine whether the molecular mass of amylose has a significant impact on the physical properties of starch.…”
Section: Physicochemical Analysis Of Potato Starchesmentioning
confidence: 99%
“…Morita et al (2002a) also reported that the high amylose wheat flour had lower gelatinization temperature and maximum viscosity than the waxy and non-waxy wheat flours. In contrast, the lower amylose content of wheat flour showed higher peak and lower final viscosity as reported by Zeng et al (1997). The pasting properties of wheat flour were also affected by the oe-amylase activities (Shuey & Tipples, 1982).…”
Section: Resultsmentioning
confidence: 84%